Mood states effect retrieval not encoding in item-method directed forgetting. Issue 4 (19th May 2021) - Goernert, Phillip N.; Corenblum, Barry; Watier, Nicholas
ABSTRACT: Three experiments examined the influence of mood state on item-method directed forgetting. In Experiments 1 and 2, happy, sad or neutral mood states were induced before the study or in Experiment 3 before retrieval. There were no significant effects of mood on memory in Experiments 1 or directed forgetting costs and benefits in Experiment 2. In Experiment 3, mood states influenced costs and benefits of directed forgetting among happy and neutral participants and costs alone among sad participants. There were no changes in the overall recall of remember-cued items when mood states were induced before or after the study. Explanations for the effect of mood on the retrieval of remember- or forget-cued items are discussed. Moods dissipate when induced prior to encoding, but appear to influence memory when induced prior to retrieval.